World biodiesel policies and production - Kumar, Ashok, 1949-; Joo, Hyunsoo (Chemical engineer) (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
"This book presents the evolution of biodiesel technologies integrated with government policies of major biodiesel producing countries with their backgrounds, impacts, changes and other energy forms. Biodiesel feedstock and biodiesel production technologies including green algae and methanol are presented in separate chapters. Changes in the feedstock types and the corresponding technologies are presented, and their impacts on the biodiesel policies are explained. The life cycle analysis (LCA) of biodiesel is presented and the findings are given for different feedstocks in terms of greenhouse gases, energy, and other impact categories, related to biodiesel policy, research, and development"--
OCLC-licensed vendor bibliographic record.
Keywords: Biodiesel fuels; Biodiesel fuels industry -- Government policy; SCIENCE / Biotechnology; SCIENCE / Energy; TECHNOLOGY / Engineering / Civil